Characterization of thin oxide layers formed by Ti-Nb alloy anodization - R.R. Santos; C.N. Elias; E.A. Ferreira; J.A.O. Huguenin; E.E. Farias; M.L. de Souza; L. da Silva (Journal of Materials Research and Technology)
Ti-Nb alloys are gaining more prominence in the industrial and scientific environment due to their high biocompatibility, mechanical strength/weight ratio, and exceptional corrosion resistance compared to other metallic materials. Metals exhibiting this passivation characteristic are known as metal valves and may exhibit semiconductive or insulating oxides. Controlling the growth of distinct thickness layer films is possible through tunning anodization conditions. In this work, a Ti-Nb binary system is anodized, and the grown oxide layer is comprehensively characterized using ellipsometry based on its optical properties and thickness at different applied potentials. Confocal Microscopy assessed their surface roughness, and SEM/EDS probed the surface material's elemental composition. CF-LIBS successfully confirmed the 70/30 composition of the Ti-Nb alloy. Raman spectra have detected the presence of amorphous TiO2 and Nb2O5 at potentials 80 V, 100 V, and 120 V. Finally, a linear dependence of the oxide thickness with the applied potential was observed.